The drunkard - Liu, Yichang, 1918-2018 (Hong Kong literature series, 2020)
The Drunkard is one of the first full-length stream-of-consciousness novels written in Chinese. It has been called the Hong Kong novel, and was first published in 1962 as a serial in a Hong Kong evening paper. As the unnamed Narrator, a writer at odds with a philistine world, sinks to his drunken nadir, his plight can be seen to represent that of a whole intelligentsia, a whole culture, degraded by the brutal forces of history: the Second Sino-Japanese War and the rampant capitalism of postwar Hong Kong. The often surrealistic description of the Narrator's inexorable descent through the seedy bars and nightclubs of Hong Kong, of his numerous encounters with dance-girls and his ever more desperate bouts of drinking, is counterpointed by a series of wide-ranging literary essays, analysing the Chinese classical tradition, the popular culture of China and the West, and the modernist movement in Western and Chinese literature. The ambiance of Hong Kong in the early 1960s is graphically evoked in this powerful and poignant novel, which takes the reader to the very heart of Hong Kong. Hong Kong director Freddie Wong made a fine film version of the novel in 2010.